The Mbeki Legacy - Pottinger, Brian; Pottinger, Brian (Penguin Random House South Africa, 2010)
In September 2008, Thabo Mbeki was ?recalled? as president of South Africa, seven months before his term was due to end. This book takes stock of Mbeki?s presidency, by focusing on a simple question: how has South Africa prospered or weakened under his stewardship? The Mbeki Legacy considers how Mbeki consolidated power and why he was defeated at the ANC?s 2007 Polokwane conference. It weighs up the successes of his macro-economic policies and his shortcomings in the fields of crime fighting, education and health. From the arms deal to the electricity crisis, it investigates the effects of corruption and mismanagement. The book also explores the impact of land reform, black economic empowerment and ?quiet diplomacy? towards Zimbabwe. Seasoned writer and analyst Brian Pottinger has sifted through reams of facts and statistics to produce a compelling, accessible and authoritative analysis of Mbeki?s South Africa. This updated edition covers events up to the 2009 election and Jacob Zuma?s first State of the Nation address, and offers additional insights into the post-Mbeki era.